Following the Crowd—Does Crowdfunding Affect Venture Capitalists' Selection of Entrepreneurial Ventures?. (1st October 2019) - Thies, Ferdinand; Huber, Alexander; Bock, Carolin; Benlian, Alexander; Kraus, Sascha
Abstract : Given the increasing popularity of crowdfunding as a new means to finance entrepreneurial ventures, we assess whether and how crowdfunding campaign‐specific signals that affect campaign success influence venture capitalists' selection decisions in ventures' follow‐up funding process. Our study relies on cross‐referencing a proprietary data set of 56, 000 crowdfunding campaigns that ran on Kickstarter between 2009 and 2016 with 100, 000 investments in the same period from the Crunchbase data set. Drawing on signaling theory and the microfinance literature, our empirical findings reveal that a successful crowdfunding campaign leads to a higher likelihood to receive follow‐up venture capital (VC) financing, and that there exists an inverted U‐shaped relationship between the funding‐ratio and the probability to receive VC funding. Further, we find statistical evidence that an endorsement by the platform provider has a likewise positive impact on the receipt of VC. Contrary to our expectations, word‐of‐mouth volume seems to be a negligible factor when it comes to follow‐up VC financing. Our results support the view that crowdfunding signals are factored into the VC's funding decision in order to evaluate the potential of entrepreneurial ventures.